Enzyme assisted degradation of potential soy protein allergens with special emphasis on the technofunctionality and the avoidance of a bitter taste formation. (May 2016) - Meinlschmidt, P.; Schweiggert-Weisz, U.; Brode, V.; Eisner, P.
Abstract: Soy protein hydrolysates are often rejected by consumers due to their unpleasant bitter taste. In the present study, soy protein isolate (SPI) was hydrolyzed using five proteases and combinations thereof to prevent bitterness. Hydrolysis was performed as one- and two-step process and the extent of hydrolysis was evaluated by SDS-PAGE and degree of hydrolysis analyses. Enzymatic hydrolysis performed as both, one- and two-step process, increased the degree of hydrolysis from initially 2.1% up to 30%. Most peptides generated were < 20 kDa and major soybean allergens (glycinin, β-conglycinin) were effectively degraded as shown by SDS-PAGE and liquid chromatography mass spectrometry (LC-MS/MS) analyses. The bitterness of SPI hydrolysates was evaluated by a sensory panel on a 10-cm continuous scale, ranging from 0 (no perception) to 10 (strong perception). Bitterness of the resulting hydrolysates was remarkably reduced to a minimum of 1.3 compared to unhydrolyzed SPI with a bitterness intensity of 2.8. Hydrolysates showed increased protein solubility at both pH 4.0 and 7.0, emulsifying capacity up to 810 mL g −1 and foaming activity up to 2706%. The study shows that enzyme combinations are an effective approach to produce hypoallergenic soy hydrolysates that combine low bitterness and superior techno-functional properties. Highlights: Effect of various enzyme combinations on the reduction of bitterness was studied. Major soy allergens (glycinin, β-conglycinin) were effectively degraded. Bitterness of hydrolysates was significantly ( P  < 0.05) decreased. Superior techno-functional properties, particularly emulsifying capacity, were achieved.